Teori dan Metodologi Sanad Hadis: Kajian Jarḥ wa Ta’dīl - Imaduddin, Muhammad; Akbar, M Khairul Hafiz (Journal of Hadith Studies, 2023)
The status of hadith as a foundational source of Islamic law necessitates rigorous criticism and verification from various dimensions. This imperative becomes particularly significant in light of the proliferation of mawḍūʿ (fabricated) hadiths, which increased substantially following the era of Fitnah. The widespread circulation of such fabrications resulted in the merging of spurious reports with authentic traditions, thereby complicating the process of authentication. In this context, the role of hadith transmitters (narrators) emerges as a pivotal element in determining the validity of a hadith, wherein the assessment of a narrator’s credibility is essential. The discipline of jarḥ wa taʿdīl provides a systematic and methodological framework established by classical scholars to evaluate the reliability of narrators. As socio-religious contexts continue to evolve and knowledge becomes increasingly digitized, the urgency of revisiting and recontextualizing this field becomes more apparent. This study seeks to map the scholarly discourse on jarḥ wa taʿdīlby analyzing academic works published between 2016 and 2023. Employing the Systematic Literature Review (SLR) method, this research reveals that the methodological development within jarḥ wa taʿdīl studies remains largely stagnant, with the majority of contemporary literature focusing on definitional aspects, historical trajectories, foundational principles, and classical applications as articulated by early Islamic scholars. However, the study also identifies emerging trends that suggest potential areas of innovation. These include the application of jarḥ wa taʿdīl principles in contemporary religious and social contexts, as well as a growing interest in digital methodologies for hadith evaluation. Such developments highlight the need for sustained and methodologically robust scholarly efforts aimed at revitalizing the study of jarḥ wa taʿdīl and adapting its principles to contemporary challenges.